2006
DOI: 10.1158/1055-9965.epi-05-0916
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Full Colon Evaluation for a Positive Fecal Occult Blood Test

Abstract: Background: Failure to appropriately evaluate a positive cancer screening test may negate the value of doing that test. The primary aim of this study was to explore the factors associated with undergoing a full colon evaluation for a positive fecal occult blood test (FOBT) in a single Veterans Affairs center. Methods: Medical records of consecutive patients ages z50 years, who had a positive screening FOBT from March 2000 to February 2001, were abstracted. Patient demographics, dates of ordering and doing foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 19 publications
4
94
4
Order By: Relevance
“…Second, while the use of FOBT as the primary screening mode in VA has been successful, it is critical to ensure that positive FOBTs are appropriately followed up with diagnostic colonoscopy and to ensure that Black patients are as likely as white patients to receive appropriate follow-up. Two recent studies conducted in the VA, including one study based on a nationally representative cohort of VA patients, 30,73 suggest that, although follow-up rates are similar for Black and White veterans, they are disappointingly low for both groups. Finally, there is a need for additional research to understand the "reverse" disparities we found among less advantaged, White veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while the use of FOBT as the primary screening mode in VA has been successful, it is critical to ensure that positive FOBTs are appropriately followed up with diagnostic colonoscopy and to ensure that Black patients are as likely as white patients to receive appropriate follow-up. Two recent studies conducted in the VA, including one study based on a nationally representative cohort of VA patients, 30,73 suggest that, although follow-up rates are similar for Black and White veterans, they are disappointingly low for both groups. Finally, there is a need for additional research to understand the "reverse" disparities we found among less advantaged, White veterans.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] We examined a broad set of predictors, including patient and health system factors, as well as those related to the clinical decision-making process. While health systems may implicitly contribute to poor follow-up via the absence of systems to identify abnormal results requiring follow-up, 32 our health system utilizes a system of quarterly feedback reports to physicians identifying patients in need of additional evaluation, lessening the impact of this issue.…”
Section: Discussionmentioning
confidence: 99%
“…15 Unfortunately, many patients with a positive fecal occult blood test (FOBT) result do not undergo appropriate follow-up diagnostic evaluation. [16][17][18][19][20][21][22] This failure to "close the loop" represents a significant lapse in care for these high risk patients, as up to 40% of patients with a positive fecal occult blood test result have either early colorectal cancer or a large adenoma identified on follow-up colonoscopy. 9,23 The reasons for this gap in care for colorectal cancer screening are likely related to a combination of physician, patient, and systems factors.…”
mentioning
confidence: 99%
“…Nonetheless, the reliability of our algorithm was substantially higher than that reported in prior work using administrative data. 27,28 Fourth, procedures and diagnoses obtained from non-VHA providers are not represented in our data set. Fifth, because we selected only one index test per patient, our results do not allow for the possibility that some patients may have been inappropriately screened multiple times.…”
Section: Rates Of Potentially Inappropriate Screeningmentioning
confidence: 99%
“…This set of codes (Appendix 2, Step 1) has been used previously to identify non-screening colonoscopies. 27,28 In Step 2, we developed a Random Forest model to classify cases not classified as non-screening in Step 1. (See Appendix 2, Step 2 for a list of variables used.)…”
mentioning
confidence: 99%